Fresno County Bar Association Luncheon: Hugh DeWitt speaker re "Star Wars: A Scientist's Perspective" - Watkins, Howard::::::::: (1986)
Robert Wright and Hugh DeWitt DeWitt -Physicist at Lawrence Livermore National Laboratory